Flexible pressure sensor containing metal oxide / carbon composite material and preparation method thereof

By using metal oxide/carbon composite material combination of melamine sponge and elastic body combination, the sensitive layer of micro -cone layer -like porous structure is formed, solving the problem of limited linear range of traditional flexible pressure sensors, and achieved high sensitivity and wide linearity. Flexible pressure sensor.

CN119354378AInactive Publication Date: 2025-01-24CHONGQING JIAOTONG UNIV

Patent Information

Application Number
CN202411438633.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The linear range of traditional piezoresistive flexible pressure sensors is limited, making it difficult to have both high sensitivity and wide linearity, which limits its use in practical applications.

Method used

The melamine sponge containing metal oxides/carbon composite materials is used as a sensitive layer, combining elastic bodies to form a multi -scale hybrid sensitive structure of micro -porous structure of micro -cone layer, improve sensitivity and expand the response range.

Benefits of technology

The high sensitivity and wide lineivity of flexible pressure sensors are realized, and the problem of limited linear range of traditional sensors is effectively solved, and the preparation methods are simple, easy to operate, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354378A_ABST
    Figure CN119354378A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flexible pressure sensors, and provides a flexible pressure sensor containing a metal oxide / carbon composite material and a preparation method thereof. The flexible pressure sensor containing the metal oxide / carbon composite material comprises flexible electrodes and a sensitive layer, the flexible electrodes comprise an upper flexible electrode and a lower flexible electrode, and the sensitive layer is located between the upper flexible electrode and the lower flexible electrode; the sensitive layer comprises elastomers and conductive sponge, the elastomers comprise an upper elastomer and a lower elastomer, and the conductive sponge is located between the upper elastomer and the lower elastomer; the conductive sponge is melamine sponge containing a metal oxide / carbon composite material. According to the invention, the sensitivity of the flexible pressure sensor is improved by using the rapid signal transduction of the micro-cone structure and the quantum tunneling effect among the multi-scale structures; the sponge serves as a flexible substrate to relieve stress concentration, and the response range of the flexible pressure sensor is expanded; the elastomer is introduced to disperse the pressure of the flexible sensor, and the linearity of the flexible sensor is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible pressure sensors, and in particular to a flexible pressure sensor containing a metal oxide / carbon composite material and a preparation method thereof. Background Art

[0002] Piezoresistive flexible pressure sensors have the advantages of high sensitivity, easy integration, and convenient signal acquisition. They are widely used in medical, artificial intelligence, electronic skin and other fields. They are also core components for human health monitoring and human-computer interaction, and have become the research frontier and hot area of ​​smart sensors.

[0003] However, due to the nonlinear piezoresistive characteristics and mechanical deformation of the sensing layer, the linear range of traditional piezoresistive flexible pressure sensors is often limited to 10-100kPa, which has become one of the important reasons restricting the further practical application of piezoresistive flexible pressure sensors. At present, the sensitivity of piezoresistive flexible pressure sensors is improved mainly by introducing topological microstructures such as pyramid structures, spherical structures and cylindrical structures in the sensing layer. However, the contact area of ​​these surface microstructures is limited, resulting in the linear range of flexible pressure sensors usually being lower than 10kPa. The improvement of the linearity of piezoresistive flexible pressure sensors is mainly achieved by introducing mixed surface microstructures in the sensing layer, but this will result in a lower sensitivity of the pressure sensor (<10kPa). -1 ), and the effectiveness of broadening the linearity is unclear.

[0004] Therefore, the development of piezoresistive flexible pressure sensors with high sensitivity and wide linearity has broad application prospects. Summary of the invention

[0005] The object of the present invention is to provide a flexible pressure sensor containing a metal oxide / carbon composite material and a preparation method thereof in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a flexible pressure sensor containing a metal oxide / carbon composite material, comprising a flexible electrode and a sensitive layer, wherein the flexible electrode comprises an upper flexible electrode and a lower flexible electrode, and the sensitive layer is located between the upper flexible electrode and the lower flexible electrode;

[0008] The sensitive layer comprises an elastomer and a conductive sponge, the elastomer comprises an upper elastomer and a lower elastomer, and the conductive sponge is located between the upper elastomer and the lower elastomer;

[0009] The conductive sponge is a melamine sponge containing a metal oxide / carbon composite material.

[0010] Preferably, the elastomer comprises one or more of polydimethylsiloxane, polyethylene, polybutylene adipate / terephthalate and polystyrene.

[0011] Preferably, the metal oxide / carbon composite material is Fe 2 O 3 / carbon composite material or ZnO / carbon composite material; the Fe 2 O 3 In the ZnO / carbon composite material or the ZnO / carbon composite material, the carbon independently includes carbon black or graphene.

[0012] Preferably, the flexible electrode is a graphene / polyimide film electrode.

[0013] Preferably, the thickness of the upper flexible electrode and the lower flexible electrode is independently 50-150 μm, the thickness of the upper elastomer and the lower elastomer is independently 100-1000 μm, and the thickness of the conductive sponge is 1.5-2.5 mm.

[0014] The present invention also provides a method for preparing the flexible pressure sensor containing the metal oxide / carbon composite material, comprising the following steps:

[0015] (1) Using graphene to laser engrave a polyimide film to obtain an upper flexible electrode and a lower flexible electrode;

[0016] (2) dropping an elastomer onto the surfaces of the upper flexible electrode and the lower flexible electrode, filtering and curing, to obtain an upper flexible electrode on which the elastomer is deposited and a lower flexible electrode on which the elastomer is deposited;

[0017] (3) mixing the metal oxide / carbon composite material with N-methylpyrrolidone and grinding the mixture to obtain a slurry, and then drying the mixture after absorbing the slurry into a sponge to obtain a conductive sponge;

[0018] (4) Placing the conductive sponge between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer, with the side deposited by the elastomer adjacent to the conductive sponge, thereby obtaining a flexible pressure sensor containing a metal oxide / carbon composite material.

[0019] Preferably, the power of the laser engraving in step (1) is 8-12 W, the speed of the laser engraving is 90-110 mm / min, and the area of ​​the laser engraving is 1-3 cm×1-3 cm; the pressure of the filtration in step (2) is <0 kPa, and the filtration time is 1-10 min; the temperature of the curing is 25-70° C., and the curing time is 0.5-2 h; the temperature of the drying in step (3) is 70-100° C., and the drying time is 6-10 h.

[0020] Preferably, in step (3), the mass volume ratio of the metal oxide / carbon composite material to N-methylpyrrolidone is 5 g: 0.5-1 mL;

[0021] The metal oxide / carbon composite material is Fe 2 O 3 The preparation method of the FeCl / carbon composite material comprises: 3 6H 2 O、Na 2 SO 4 , carbon and water are mixed to react I to obtain precursor I, which is dried and calcined to obtain Fe 2 O 3 / Carbon composite materials;

[0022] When the metal oxide / carbon composite material is a ZnO / carbon composite material, the preparation method comprises: 3 ) 2 6H 2 O, cyclohexamethylenetetramine, carbon and water are mixed to carry out reaction II to obtain precursor II, and precursor II is dried and calcined to obtain ZnO / carbon composite material.

[0023] Preferably, the FeCl 3 6H 2 O、Na 2 SO 4 , the mass volume ratio of carbon and water is 90-110 mg:40-55 mg:80-100 mg:30 mL; the temperature of reaction I is 100-140° C., and the time of reaction I is 4-8 h;

[0024] The Zn(NO 3 ) 2 6H 2 The mass volume ratio of O, hexamethylenetetramine, carbon and water is 10-14 g: 0.3-0.8 g: 10-24 g: 40 mL; the temperature of the reaction II is 80-120° C., and the time of the reaction II is 6-10 h.

[0025] Preferably, the drying temperature is independently 50-70°C, and the drying time is independently 6-10h; the calcination temperature is independently 300-500°C, the calcination time is independently 2-5h, and the calcination heating rate is independently 2-5°C / min.

[0026] The beneficial effects of the present invention include the following:

[0027] The sea urchin-shaped sensitive material (metal oxide / carbon composite material) of the present invention forms a multi-scale hybrid sensitive structure with a micro-cone layered porous structure with a sponge flexible matrix, and the sensitivity of the flexible pressure sensor is improved by utilizing the advantages of the micro-cone structure with fast signal transduction and the quantum tunneling effect between the multi-scale structures; the sponge with a layered porous structure is used as a flexible substrate to effectively relieve stress concentration, thereby expanding the response range of the flexible pressure sensor; by introducing an elastomer as a stiffness regulator, the pressure acting on the flexible sensor is effectively dispersed, the linearity of the flexible sensor is widened, and the problem that the current flexible pressure sensor is difficult to have both high sensitivity and a wide linear range is effectively solved. The preparation method of the present invention is simple, easy to operate, low in cost and easy to repeat. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Fe prepared in Example 1 2 O 3 / SEM images of carbon black composites;

[0029] Figure 2 The scanning electron microscope images of the conductive sponge and melamine sponge prepared in Example 1, wherein a and b are scanning electron microscope images of the melamine sponge, and c and d are scanning electron microscope images of the conductive sponge;

[0030] Figure 3 It is a schematic structural diagram of a flexible pressure sensor containing a metal oxide / carbon composite material of the present invention;

[0031] Figure 4 is a flow chart of the preparation of the flexible electrode of the present invention;

[0032] Figure 5 This is a working principle diagram of the flexible pressure sensor containing the metal oxide / carbon composite material of the present invention;

[0033] Figure 6 This is the sensitivity curve of the flexible pressure sensor prepared in Example 2 (conductive sponge, the elastomer is polystyrene);

[0034] Figure 7 The sensitivity curve of the flexible pressure sensor prepared in Comparative Example 1 (conductive sponge, the elastomer is aluminum oxide);

[0035] Figure 8 For comparative example 2 (containing a single metal oxide Fe 2 O 3 melamine sponge), Comparative Example 3 (containing a single metal oxide SnO 2 Sensitivity curve of the flexible pressure sensor prepared by melamine sponge.

[0036] Fig. 9This is the sensitivity curve of the flexible pressure sensor prepared in Comparative Example 4 (melamine sponge containing only carbon black). DETAILED DESCRIPTION

[0037] The present invention provides a flexible pressure sensor containing a metal oxide / carbon composite material, comprising a flexible electrode and a sensitive layer, wherein the flexible electrode comprises an upper flexible electrode and a lower flexible electrode, and the sensitive layer is located between the upper flexible electrode and the lower flexible electrode;

[0038] The sensitive layer comprises an elastomer and a conductive sponge, the elastomer comprises an upper elastomer and a lower elastomer, and the conductive sponge is located between the upper elastomer and the lower elastomer;

[0039] The conductive sponge is a melamine sponge containing a metal oxide / carbon composite material.

[0040] In the present invention, the structure of the flexible pressure sensor containing the metal oxide / carbon composite material is as follows Figure 3 As shown; the working principle of the flexible pressure sensor containing metal oxide / carbon composite material is as follows Figure 5 As shown, when pressure is applied to the flexible pressure sensor, the sponge skeleton is compressed, forming a conductive path and generating current; when the pressure is released, the sponge skeleton returns to its initial state.

[0041] In the present invention, the elastomer preferably comprises one or more of polydimethylsiloxane, polyethylene, polybutylene adipate / terephthalate and polystyrene.

[0042] In the present invention, the elastomer is preferably in liquid state.

[0043] In the present invention, the metal oxide / carbon composite material is preferably Fe 2 O 3 / carbon composite material or ZnO / carbon composite material; the Fe 2 O 3 In the ZnO / carbon composite material or the ZnO / carbon composite material, the carbon independently preferably includes carbon black or graphene.

[0044] In the present invention, the metal oxide / carbon composite material is preferably a sea urchin-like structure, and the conductive sponge is preferably a micro-cone layered porous structure.

[0045] In the present invention, the flexible electrode is preferably a graphene / polyimide film electrode.

[0046] In the present invention, the thickness of the upper flexible electrode and the lower flexible electrode is preferably 50 to 150 μm, more preferably 80 to 120 μm, and more preferably 100 μm; the thickness of the upper elastomer and the lower elastomer is preferably 100 to 1000 μm, more preferably 300 to 700 μm, and more preferably 500 μm; the thickness of the conductive sponge is preferably 1.5 to 2.5 mm, and more preferably 2 mm.

[0047] The present invention also provides a method for preparing the flexible pressure sensor containing the metal oxide / carbon composite material, comprising the following steps:

[0048] (1) Using graphene to laser engrave a polyimide film to obtain an upper flexible electrode and a lower flexible electrode;

[0049] (2) dropping an elastomer onto the surfaces of the upper flexible electrode and the lower flexible electrode, filtering and curing, to obtain an upper flexible electrode on which the elastomer is deposited and a lower flexible electrode on which the elastomer is deposited;

[0050] (3) mixing the metal oxide / carbon composite material with N-methylpyrrolidone and grinding the mixture to obtain a slurry, and then drying the mixture after absorbing the slurry into a sponge to obtain a conductive sponge;

[0051] (4) Placing the conductive sponge between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer, with the side deposited by the elastomer adjacent to the conductive sponge, thereby obtaining a flexible pressure sensor containing a metal oxide / carbon composite material.

[0052] In the present invention, the power of the laser engraving in step (1) is preferably 8-12 W, more preferably 9-11 W, and more preferably 10 W; the speed of the laser engraving is preferably 90-110 mm / min, more preferably 95-105 mm / min, and more preferably 100 mm / min; the area of ​​the laser engraving is preferably 1-3 cm×1-3 cm, more preferably 1.5-2.5 cm×1.5-2.5 cm, and more preferably 2 cm×2 cm; the pressure of the filtration in step (2) is preferably <0 kPa; the filtration time is preferably 1-10 min, more preferably 3-8 min, and more preferably 5 min; the curing temperature is preferably 25-70°C, more preferably 40-60°C, and more preferably 50°C; the curing time is preferably 0.5-2 h, and more preferably 1-1.5 h; the drying temperature in step (3) is preferably 70-100°C, more preferably 80-90°C; the drying time is preferably 6-10 h, more preferably 7-9 h, and more preferably 8 h.

[0053] In the present invention, the preparation process of the upper flexible electrode and the lower flexible electrode in step (1) is as follows: Figure 4 shown.

[0054] In the present invention, the mass volume ratio of the metal oxide / carbon composite material to N-methylpyrrolidone in step (3) is preferably 5 g: 0.5-1 mL, more preferably 5 g: 0.6-0.9 mL, and more preferably 5 g: 0.7-0.8 mL;

[0055] The metal oxide / carbon composite material is Fe 2 O 3 The preparation method of the FeCl / carbon composite material preferably comprises: 3 6H 2 O、Na 2 SO 4 , carbon and water are mixed to react I to obtain precursor I, which is dried and calcined to obtain Fe 2 O 3 / Carbon composite materials;

[0056] When the metal oxide / carbon composite material is a ZnO / carbon composite material, the preparation method preferably comprises: 3 ) 2 6H 2 O, cyclohexamethylenetetramine, carbon and water are mixed to carry out reaction II to obtain precursor II, and precursor II is dried and calcined to obtain ZnO / carbon composite material.

[0057] In the present invention, the metal oxide / carbon composite material is Fe 2 O 3 In the preparation method of the carbon / carbon composite material, the mixing is preferably carried out under magnetic stirring conditions, and the rotation speed of the magnetic stirring is preferably 500-1000r / min, and more preferably 600-800r / min; the time of the magnetic stirring is preferably 20-40min, and more preferably 30min.

[0058] In the present invention, in the preparation method when the metal oxide / carbon composite material is a ZnO / carbon composite material, the mixing is preferably carried out under magnetic stirring conditions, and the rotation speed of the magnetic stirring is preferably 500-1000r / min, and more preferably 600-800r / min; the time of magnetic stirring is preferably 20-40min, and more preferably 30min.

[0059] In the present invention, in the preparation method when the metal oxide / carbon composite material is a ZnO / carbon composite material, it is preferred to adjust the pH value of the mixed solution before reacting, the reagent used to adjust the pH value of the mixed solution is preferably ammonia water, and the pH value of the mixed solution is preferably adjusted to 8-10, and more preferably adjusted to 9; the dripping rate of ammonia water is preferably 50-70 drops / min, and more preferably 60 drops / min; the mass fraction of ammonia water is preferably 20-30%, and more preferably 25%.

[0060] In the present invention, the FeCl 3 6H 2 O、Na 2 SO 4 , the mass volume ratio of carbon and water is preferably 90-110mg:40-55mg:80-100mg:30mL, more preferably 95-105mg:45-50mg:85-95mg:30mL, more preferably 103mg:48mg:90mg:30mL; the temperature of the reaction I is preferably 100-140°C, more preferably 110-130°C, more preferably 120°C; the time of the reaction I is preferably 4-8h, more preferably 5-7h, more preferably 6h;

[0061] The Zn(NO 3 ) 2 6H 2 The mass volume ratio of O, hexamethylenetetramine, carbon and water is preferably 10-14g:0.3-0.8g:10-24g:40mL, further preferably 11-13g:0.5-0.7g:15-20g:40mL, more preferably 12g:0.56g:18g:40mL; the temperature of the reaction II is preferably 80-120°C, further preferably 90-110°C, more preferably 100°C; the time of the reaction II is preferably 6-10h, further preferably 7-9h, more preferably 8h.

[0062] In the present invention, the drying temperature is independently preferably 50-70°C, more preferably 55-65°C, and more preferably 60°C; the drying time is independently preferably 6-10h, more preferably 7-9h, and more preferably 8h; the calcination temperature is independently preferably 300-500°C, more preferably 350-450°C, and more preferably 400°C; the calcination time is independently preferably 2-5h, and more preferably 3-4h; the calcination heating rate is independently preferably 2-5°C / min, and more preferably 3-4°C / min.

[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] 0.103 g FeCl 3 6H 2 O, 0.048 g Na 2 SO 4 , 0.09g carbon black and 30mL deionized water were mixed, and magnetic stirring was carried out at a speed of 600r / min for 30min to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 120°C for 6h. After the reaction, the reaction solution was cooled to room temperature, filtered at <0kPa for 5min, and the product was washed with anhydrous ethanol and deionized water in turn to obtain a precursor powder. The precursor powder was placed in a vacuum drying oven at 60°C (vacuum degree is <0kPa) and dried for 8h. The dried powder was transferred to a tubular furnace, heated to 450°C at a heating rate of 3°C / min under air conditions, and calcined for 3h to obtain a sea urchin-shaped Fe 2 O 3 / carbon black composite materials.

[0066] The polyimide film was laser engraved using graphene (engraving power of 10 W, speed of 100 mm / min, area of ​​2 cm×2 cm) to obtain an upper flexible electrode with a thickness of 100 μm and a lower flexible electrode with a thickness of 100 μm.

[0067] Liquid poly(butylene adipate / terephthalate) was dropped onto the surface of the upper flexible electrode and the lower flexible electrode respectively, and filtered at <0 kPa for 5 minutes, followed by curing at 50°C for 0.5 hours to obtain an elastomer-deposited upper flexible electrode and an elastomer-deposited lower flexible electrode with an elastomer thickness of 500 μm.

[0068] Fe 2 O 3 The / carbon black composite material was ground for 10 min, and then N-methylpyrrolidone (Fe 2 O 3 / The mass volume ratio of carbon black composite material to N-methylpyrrolidone is 5g:0.7mL), and then ground again to make slurry. Take a 2cm×2cm×2cm melamine sponge, wash it with anhydrous ethanol and ultrapure water respectively, and then dry it at 50℃ for 4h. Then soak the dried melamine sponge in the slurry for 5min, take it out, weigh it and record it, repeat the soaking, taking out and weighing steps until the weight does not change, and get a melamine sponge full of slurry. Place the melamine sponge full of slurry in a blast drying oven and dry it at 80℃ for 8h to get a conductive sponge with a micro-cone layered porous structure with a thickness of 2cm.

[0069] The conductive sponge is placed between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer (the side of the elastomer deposition is adjacent to the conductive sponge), wires are led out from both ends of the upper flexible electrode and the lower flexible electrode and fixed with conductive silver paste, and then packaged with PI tape to obtain a flexible pressure sensor containing a metal oxide / carbon composite material.

[0070] The sea urchin-shaped Fe 2 O 3 / carbon black composites such as Figure 1 As shown, where C represents carbon black.

[0071] The scanning electron microscope images of the conductive sponge and melamine sponge with micro-cone layered porous structure of this embodiment are as follows: Figure 2 As shown, a and b are scanning electron microscope images of melamine sponge, and c and d are scanning electron microscope images of conductive sponge. Figure 2 It can be seen that the melamine sponge is composed of interconnected skeletons to form a hexagonal pore structure, while the surface of the skeleton in the conductive sponge is rough. The composite material is attached to the sponge skeleton, but the microstructure of the sponge has not changed and still maintains a layered porous structure.

[0072] Example 2

[0073] The polybutylene adipate / terephthalate in Example 1 was replaced by polystyrene, and the rest was the same as in Example 1.

[0074] Example 3

[0075] The Fe 2 O 3 The / carbon black composite material is replaced by the ZnO / carbon black composite material, and the rest is the same as in Example 1.

[0076] The preparation method of ZnO / carbon black composite material is as follows: 12g Zn(NO 3 ) 2 6H 2O, 0.56g cyclohexamethylenetetramine, 18g carbon black and 40mL deionized water were mixed, and magnetic stirring was performed at a speed of 800r / min for 30min to obtain a mixed solution; 25% ammonia water was added to the mixed solution at a speed of 60 drops / min until the pH value of the mixed solution was 9; the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 100°C for 8h. After the reaction, the reaction solution was cooled to room temperature, filtered at <0kPa for 3min, and the product was washed with anhydrous ethanol and deionized water in turn to obtain a precursor powder. The precursor powder was placed in a vacuum drying oven at 60°C (vacuum degree <0kPa) and dried for 8h, and the dried powder was transferred to a tubular furnace, heated to 450°C at a heating rate of 3°C / min under air conditions, and calcined for 3h to obtain a sea urchin-shaped ZnO / carbon black composite material.

[0077] Example 4

[0078] 0.095 g FeCl 3 6H 2 O, 0.04gNa 2 SO 4 , 0.085g carbon black and 30mL deionized water were mixed, and magnetic stirring was carried out at a speed of 800r / min for 20min to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 100°C for 8h. After the reaction, the reaction solution was cooled to room temperature, filtered at <0kPa for 7min, and the product was washed with anhydrous ethanol and deionized water in turn to obtain a precursor powder. The precursor powder was placed in a vacuum drying oven at 50°C (vacuum degree is <0kPa) and dried for 10h. The dried powder was transferred to a tubular furnace, heated to 400°C at a heating rate of 3°C / min under air conditions, and calcined for 5h to obtain a sea urchin-shaped Fe 2 O 3 / carbon black composite materials.

[0079] The polyimide film was laser engraved using graphene (engraving power of 8 W, speed of 110 mm / min, area of ​​3 cm×3 cm) to obtain an upper flexible electrode with a thickness of 50 μm and a lower flexible electrode with a thickness of 50 μm.

[0080] Liquid polyethylene was dropped onto the surface of the upper flexible electrode and the lower flexible electrode respectively, and filtered at <0 kPa for 8 minutes, followed by curing at 25°C for 2 hours to obtain an elastomer-deposited upper flexible electrode and an elastomer-deposited lower flexible electrode with an elastomer thickness of 1000 μm.

[0081] Fe 2 O 3 The / carbon black composite material was ground for 10 min, and then N-methylpyrrolidone (Fe2 O 3 / carbon black composite material and N-methylpyrrolidone mass volume ratio of 5g: 1mL), and grind again to make slurry. Take a 2cm×2cm×2cm melamine sponge, wash it with anhydrous ethanol and ultrapure water respectively, and then dry it at 60℃ for 3h. Then soak the cleaned melamine sponge in the slurry for 5min, take it out and weigh it and record it. Repeat the soaking and weighing steps until the weight does not change, and get a melamine sponge full of slurry. Place the melamine sponge full of slurry in a blast drying oven and dry it at 70℃ for 10h to get a conductive sponge with a micro-cone layered porous structure with a thickness of 2cm.

[0082] The conductive sponge is placed between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer (the side of the elastomer deposition is adjacent to the conductive sponge), wires are led out from both ends of the upper flexible electrode and the lower flexible electrode and fixed with conductive silver paste, and then packaged with PI tape to obtain a flexible pressure sensor containing a metal oxide / carbon composite material.

[0083] Example 5

[0084] 14 g Zn(NO 3 ) 2 6H 2 O, 0.3g cyclohexamethylenetetramine, 10g carbon black and 40mL deionized water were mixed, and magnetic stirring was performed at a speed of 500r / min for 30min to obtain a mixed solution; 20% ammonia water was added to the mixed solution at a speed of 50 drops / min until the pH value of the mixed solution was 10; the mixed solution was transferred to a polytetrafluoroethylene reactor and reacted at 80°C for 10h. After the reaction, the reaction solution was cooled to room temperature, filtered at <0kPa for 3min, and the product was washed with anhydrous ethanol and deionized water in turn to obtain a precursor powder. The precursor powder was placed in a vacuum drying oven at 70°C (vacuum degree <0kPa) and dried for 6h, and the dried powder was transferred to a tubular furnace, heated to 500°C at a heating rate of 3°C / min under air conditions, and calcined for 2h to obtain a sea urchin-shaped ZnO / carbon black composite material.

[0085] The polyimide film was laser engraved using graphene (engraving power of 12 W, speed of 90 mm / min, area of ​​2 cm×2 cm) to obtain an upper flexible electrode with a thickness of 150 μm and a lower flexible electrode with a thickness of 150 μm.

[0086] Liquid polydimethylsiloxane was dropped onto the surface of the upper flexible electrode and the lower flexible electrode respectively, and filtered at <0 kPa for 1 min, and then cured at 70°C for 1 h to obtain an elastomer-deposited upper flexible electrode and an elastomer-deposited lower flexible electrode with an elastomer thickness of 100 μm.

[0087] The ZnO / carbon black composite material was ground for 10 minutes, and then N-methylpyrrolidone (the mass volume ratio of the ZnO / carbon black composite material to N-methylpyrrolidone was 5g:0.5mL) was added dropwise, and the mixture was ground again to form a slurry. A 2cm×2cm×2cm melamine sponge was taken, washed with anhydrous ethanol and ultrapure water, respectively, and dried at 40°C for 5 hours. The washed melamine sponge was then soaked in the slurry for 5 minutes, taken out and weighed, and recorded. The soaking, taking out and weighing steps were repeated until the weight did not change, and a melamine sponge fully absorbed with the slurry was obtained. The melamine sponge fully absorbed with the slurry was placed in a forced air drying oven and dried at 100°C for 6 hours to obtain a conductive sponge with a micro-cone layered porous structure with a thickness of 2 cm.

[0088] The conductive sponge is placed between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer (the side of the elastomer deposition is adjacent to the conductive sponge), wires are led out from both ends of the upper flexible electrode and the lower flexible electrode and fixed with conductive silver paste, and then packaged with PI tape to obtain a flexible pressure sensor containing a metal oxide / carbon composite material.

[0089] Comparative Example 1

[0090] The polystyrene in Example 2 is replaced by alumina, and the rest is the same as in Example 2.

[0091] Comparative Example 2

[0092] The Fe in Example 2 2 O 3 / carbon black composites replaced by Fe 2 O 3 , the rest is the same as Example 2.

[0093] Comparative Example 3

[0094] The Fe in Example 2 2 O 3 / carbon black composites replaced by SnO 2 , the rest is the same as Example 2.

[0095] Comparative Example 4

[0096] The Fe in Example 2 2 O 3 The / carbon black composite material is replaced by carbon black, and the rest is the same as in Example 2.

[0097] The flexible pressure sensors of Example 2 and Comparative Examples 1 to 4 were placed on a universal testing machine (the application speed of the universal testing machine was 2 mm / min) and connected to a digital source meter to collect resistance signals. The test results are shown in Figures 6 to 9 .

[0098] Depend on Figure 6 , 7 It can be seen that the linearity of the flexible pressure sensor with polystyrene as the elastomer is significantly better than that of the flexible pressure sensor with metal oxide as the elastomer. Using polystyrene as the elastomer greatly increases the compressibility, effectively expands the linear range of the flexible sensor, and achieves high sensitivity and wide linearity of the flexible pressure sensor.

[0099] Depend on Figure 6 , 8 9 It can be seen that the linearity of the flexible pressure sensor comprising the metal oxide / carbon composite material of the present invention is significantly better than that of the flexible pressure sensor containing a single metal oxide or carbon black. This is because the conductivity of a single metal oxide is weak and the change of the current signal is limited. The addition of carbon can effectively improve the conductivity of the metal oxide, thereby enhancing the sensitivity of the metal oxide / carbon composite material.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flexible pressure sensor containing a metal oxide / carbon composite material, characterized in that: The flexible electrode comprises an upper flexible electrode and a lower flexible electrode, and the sensitive layer is located between the upper flexible electrode and the lower flexible electrode; The sensitive layer comprises an elastomer and a conductive sponge, the elastomer comprises an upper elastomer and a lower elastomer, and the conductive sponge is located between the upper elastomer and the lower elastomer; The conductive sponge is a melamine sponge containing a metal oxide / carbon composite material.

2. The flexible pressure sensor containing a metal oxide / carbon composite material according to claim 1, characterized in that: The elastomer comprises one or more of polydimethylsiloxane, polyethylene, polybutylene adipate / terephthalate and polystyrene.

3. The flexible pressure sensor containing a metal oxide / carbon composite material according to claim 1 or 2, characterized in that: The metal oxide / carbon composite material is a Fe2O3 / carbon composite material or a ZnO / carbon composite material; in the Fe2O3 / carbon composite material or the ZnO / carbon composite material, carbon independently comprises carbon black or graphene.

4. The flexible pressure sensor containing a metal oxide / carbon composite material according to claim 3, characterized in that: The flexible electrode is a graphene / polyimide film electrode.

5. The flexible pressure sensor containing a metal oxide / carbon composite material according to claim 4, characterized in that: The thickness of the upper flexible electrode and the lower flexible electrode is independently 50-150 μm, the thickness of the upper elastomer and the lower elastomer is independently 100-1000 μm, and the thickness of the conductive sponge is 1.5-2.5 mm.

6. The method for preparing a flexible pressure sensor containing a metal oxide / carbon composite material according to any one of claims 1 to 5, characterized in that: The following steps are included: (1) Using graphene to laser engrave a polyimide film to obtain an upper flexible electrode and a lower flexible electrode; (2) dropping an elastomer onto the surfaces of the upper flexible electrode and the lower flexible electrode, filtering and curing, to obtain an upper flexible electrode on which the elastomer is deposited and a lower flexible electrode on which the elastomer is deposited; (3) mixing the metal oxide / carbon composite material with N-methylpyrrolidone and grinding the mixture to obtain a slurry, and then drying the sponge after absorbing the slurry to obtain a conductive sponge; (4) Placing the conductive sponge between the upper flexible electrode deposited by the elastomer and the lower flexible electrode deposited by the elastomer, with the side deposited by the elastomer adjacent to the conductive sponge, thereby obtaining a flexible pressure sensor containing a metal oxide / carbon composite material.

7. The preparation method according to claim 6, characterized in that: The power of the laser engraving in step (1) is 8-12W, the speed of the laser engraving is 90-110mm / min, and the area of ​​the laser engraving is 1-3cm×1-3cm; the pressure of the filtration in step (2) is <0kPa, and the filtration time is 1-10min; the temperature of the curing is 25-70°C, and the curing time is 0.5-2h; the temperature of the drying in step (3) is 70-100°C, and the drying time is 6-10h.

8. The preparation method according to claim 6 or 7, characterized in that: In step (3), the mass volume ratio of the metal oxide / carbon composite material to N-methylpyrrolidone is 5 g: 0.5-1 mL; When the metal oxide / carbon composite material is a Fe2O3 / carbon composite material, the preparation method comprises: mixing FeCl3·6H2O, Na2SO4, carbon and water to carry out reaction I to obtain a precursor I, and drying and calcining the precursor I to obtain a Fe2O3 / carbon composite material; When the metal oxide / carbon composite material is a ZnO / carbon composite material, the preparation method comprises: mixing Zn(NO3)2·6H2O, hexamethylenetetramine, carbon and water and performing reaction II to obtain a precursor II, and drying and calcining the precursor II to obtain the ZnO / carbon composite material.

9. The preparation method according to claim 8, characterized in that: The mass volume ratio of FeCl3·6H2O, Na2SO4, carbon and water is 90-110mg:40-55mg:80-100mg:30mL; the temperature of reaction I is 100-140°C, and the time of reaction I is 4-8h; The mass volume ratio of the Zn(NO3)2·6H2O, hexamethylenetetramine, carbon and water is 10-14g:0.3-0.8g:10-24g:40mL; the temperature of the reaction II is 80-120°C, and the time of the reaction II is 6-10h.

10. The preparation method according to claim 9, characterized in that: The drying temperature is independently 50-70°C, and the drying time is independently 6-10h; the calcination temperature is independently 300-500°C, the calcination time is independently 2-5h, and the calcination heating rate is independently 2-5°C / min.

Citation Information

Patent Citations

  • High-sensitivity capacitive flexible tactile sensor based on three-dimensional porous microstructure composite dielectric layer and manufacturing method thereof

    CN109520646A

  • Metal particle modified graphene flexible sensor and preparation method and application thereof

    CN109632896A

  • Wide-range flexible resistance type pressure sensor and preparation method thereof

    CN113340484A

  • Flexible pressure sensor based on porous structure composite material and preparation method thereof

    CN115014597A

  • Flexible sensor-oriented bionic porous conductive elastic composite material and preparation method thereof

    CN118496669A

Cited By

  • Composite fiber membrane based on sea urchin-shaped pollen carbon, preparation method and application

    CN120797314A